An analysis of Pharmacy Students’ English Language needs - Roudlotun Nurul Laili; Muhammad Nashir (Universitas Sulawesi Barat, 2023)
This study investigated the English needs of Pharmacy Diploma students in order to identify the gaps in language learning and then create a new curriculum, learning strategies, methods, and the English class syllabus for special needs (ESP). Needs analysis is crucial to ensure that the learning design implemented meets the students’ needs with the hope of being able to help students academically and professionally. The method used in this study was a descriptive qualitative with the total respondents was 61 (40 active students of pharmacy diploma at STIKes Banyuwangi, 15 alumni of pharmacy diploma who had already worked, and 6 diploma pharmacy lecturers). The research instruments were questionnaire and interview. The research result showed speaking was the most difficult skill for students. Whereas, the students believed that speaking is one of the most important skills they need. The students need English which relate to Pharmacy diploma major to support their career because 76% students stated that they learn English to support their future career. There were 13 materials of English for pharmacy that must be taught to students. This research results will be used as a basis reference for developing English in pharmacy syllabus and English textbooks for pharmacy diploma students.